Surprising Bone and Soft Tissue Lesions of the Chest: Pictorial Review - Degrieck, Bert J. R.; Bazzocchi, Alberto; Verstraete, Koenraad (Seminars in Musculoskeletal Radiology, 2019)
Although plain radiographs of the chest are usually requested to evaluate the heart, lung, and mediastinum, many bone and soft tissue, metabolic, and congenital lesions can be visible presenting as surprising lesions. Thorough analysis of the lesion characteristics on the chest radiograph, eventually in conjunction with more advanced imaging techniques and in combination with the clinical findings, will lead to the correct diagnosis.
Keywords: chest radiograph; bone tumor; soft tissue tumor; incidental finding; metabolic disease